2015
DOI: 10.4081/cp.2015.814
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of a Patient Receiving a Large-Resection Hip Prosthesis Because of a Phosphaturic Mesenchymal Tumor

Abstract: Tumor-induced osteomalacia is an osteomalacic syndrome caused by a mesenchymal origin’s tumor. The diagnostic procedure takes time and extensive investigations because of the characteristics of these tumors usually small dimensioned, slowly growing, non-invasive and therefore hard to locate. The differential diagnosis is determined by a bone biopsy. Tumor’s surgical removal is the treatment of choice that leads up to a complete regression of the oncogenic malacic syndrome. In the clinical course of these patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…In their case report, Lopresti et al demonstrate how difficult and time consuming the diagnostics of tumor–induced osteomalacia can be [ 53 ]. They report a patient presenting diffuse costal and vertebral pain without any trauma over a three–year period.…”
Section: Bone Healthmentioning
confidence: 99%
“…In their case report, Lopresti et al demonstrate how difficult and time consuming the diagnostics of tumor–induced osteomalacia can be [ 53 ]. They report a patient presenting diffuse costal and vertebral pain without any trauma over a three–year period.…”
Section: Bone Healthmentioning
confidence: 99%
“…Limb salvage and preservation of joint function and the prospect for rapid mobilization are the major advantages of distal femoral reconstruction for patients that have previously undergone total knee arthroplasty. This may be especially true for older patients or those with reduced physical conditions who may be mobilized sooner when the limb is preserved [17, 37]. Joint functionality after DFR in individuals with multiple revisions is expected to be at an acceptable level [9, 10, 15, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our review of the literature on PubMed, the average time from onset of symptoms to a confirmed diagnosis of TIO often exceeds 2.5 years. [1–3,811,17,18] Definitive treatment is further delayed by an average of 5 years due to inability to find the underlying tumor due to the characteristics of being small and slow growing and being located in particular or atypical sites. [811,17,18] Typical laboratory findings include hyperphosphaturia, elevated alkaline phosphatase, and low serum 1,25-dihydroxy vitamin D in literature, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[1–3,811,17,18] Definitive treatment is further delayed by an average of 5 years due to inability to find the underlying tumor due to the characteristics of being small and slow growing and being located in particular or atypical sites. [811,17,18] Typical laboratory findings include hyperphosphaturia, elevated alkaline phosphatase, and low serum 1,25-dihydroxy vitamin D in literature, respectively. [1–3,12,13] Hypophosphatemia is secondary to inhibition of renal phosphorus reabsorption, and the vitamin D synthetic defect blocks the compensatory rise of calcitriol stimulated by the hypophosphatemia.…”
Section: Discussionmentioning
confidence: 99%